Extracellular Enzyme Activity and Its Implications for Organic Matter Cycling in Northern Chinese Marginal Seas - Li, Yi; Sun, Lin-Lin; Sun, Yuan-Yuan; Cha, Qian-Qian; Li, Chun-Yang; Zhao, Dian-Li; Song, Xiao-Yan; Wang, Min; McMinn, Andrew; Chen, Xiu-Lan; Zhang, Yu-Zhong; Qin, Qi-Long (Frontiers in Microbiology, 2019)
Extracellular enzymes, initiating the degradation of organic macromolecules, are important functional components of marine ecosystems. Measuring in situ seawater extracellular enzyme activity (EEA) can provide fundamental information for understanding the biogeochemical cycling of organic matter in the ocean. Here we investigate the patterns of EEA and the major factors affecting the seawater EEA of Chinese marginal seas. The geographic distribution of EEA along a latitudinal transect was examined and found to be associated with dissolved organic carbon. Compared with offshore waters, inshore waters had higher enzyme activity. All the tested substrates were hydrolyzed at different rates and phosphatase, β-glucosidase and protease contributed greatly to summed hydrolysis rates. For any particular enzyme activity, the contribution of dissolved to total EEA was strongly heterogenous between stations. Comparisons of hydrolysis rates of the polymers and their corresponding oligomers suggest that molecule size does not necessarily limit the turnover of marine organic matter. In addition, several typical enzyme-producing clades, such as Bacteroidetes, Planctomycetes, Chloroflexi, Roseobacter, Alteromonas, and Pseudoalteromonas, were detected in the in situ environments. These enzyme-producing clades may be responsible for the production of different enzymes. Overall, each enzyme was found to flexibly respond to environmental conditions and were linked to microbial community composition. It is likely that this activity will profoundly affect organic matter cycling in the Chinese marginal seas.